Clostridium butyricum Helps to Alleviate Inflammation in Weaned Piglets Challenged With Enterotoxigenic Escherichia coli K88 - Li, Haihua; Liu, Xuejiao; Shang, Zhiyuan; Qiao, Jiayun (Frontiers in Veterinary Science, 2021)
Background: The problem that the probiotic Clostridium butyricum (CB) alleviates ETEC K88-induced inflammation by regulating the activation of the TLR signaling pathway is not clear, thus, we carried out this study. 72 piglets (the average body weight is 7.09 ± 0.2 kg) were randomly divided three groups into 24 piglets per group. Pigs were fed a daily diet (NC, negative control), the diet tested by every day 1  109 CFU/mL ETEC K88 (PC, positive control), the basal diet supplemented with 5  105 CFU/g CB got challenge accepting ETEC K88 (PC+CB group), respectively. Results: Our results showed that CB pretreatment attenuated the effect of ETEC K88 by decreasing C-reactive protein (CRP), which was called tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) production. Histological examination revealed that CB pretreatment alleviated intestinal villi injury caused by ETEC K88 challenge. Furthermore, CB pretreatment promoted mRNA expression of the negative regulators of toll-like receptor (TLR) signaling, including myeloid differentiation factor (MyD88), toll-interacting protein (Tollip) and B cell CLL/lymphoma 3 (Bcl-3), in the intestines of ETEC K88-challenged piglets. ETEC K88-induced activation of nuclear factor kappa B (NF-κB) and nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα) was attenuated by CB pretreatment. Conclusion: These findings indicate that CB helps to maintain and strengthen the shape of intestinal villi and limits detrimental inflammatory responses, partly by inhibiting toll-like receptor 2 (TLR-2), toll-like receptor 4 (TLR-4) and toll-like receptor 5 (TLR-5) expression and inhibiting NF-κB p65, and promoting IBα activation and synergism among its negative regulators.